Hedgehog signaling is active in human prostate cancer stroma and regulates proliferation and differentiation of adjacent epithelium. Issue 16 (16th September 2013) - Wilkinson, Sarah E.; Furic, Luc; Buchanan, Grant; Larsson, Ola; Pedersen, John; Frydenberg, Mark; Risbridger, Gail P.; Taylor, Renea A.
Abstract BACKGROUND Contribution of stromal Hedgehog (Hh) signaling is evident in the prostate gland in mice, but needs translation to human tissues if Hh therapeutics are to be used effectively. Our goal was to determine if primary human prostate fibroblasts contain cilia, and respond to prostate Hh signaling. METHODS Primary human prostate cancer‐associated (CAFs), and adjacent non‐malignant (NPFs) fibroblasts isolated from human tissue specimens were analyzed using immunofluorescence, real‐time PCR, and available array data. Cell culture and tissue recombination were used to determine responsiveness of human fibroblasts to Hh pathway manipulation and the paracrine effects of stromal Hh signaling, respectively. RESULTS Prostatic fibroblasts were capable of forming primary cilia, with the capacity for active Hh signaling as seen by Smo co‐localization to the tip of the primary cilium. Expression of genes known to represent a signature of active Hh signaling in the prostate (especially Fgf5 and Igfbp6) were increased in CAFs compared to NPFs. The level of canonical Hh genes and prostate Hh signature genes were rarely synchronous; with lower doses of Purmorphamine/BMS‐833923 regulating canonical transcription factors, and higher doses effecting prostate Hh signature genes. Grafts consisting of NPFs with constitutively active Hh signaling induced increased proliferation and dedifferentiation of adjacent non‐malignant BPH‐1 epithelial cells. CONCLUSIONS These data show that human prostatic fibroblasts have the capacity for Hh signaling and manipulation. Increased expression of a signature of prostatic Hh genes in the prostate tumor microenvironment suggests a role in the epithelial transformations driving prostate cancer (PCa). Prostate 73:1810–1823, 2013. © 2013 Wiley Periodicals, Inc.